Diversity of genetic basis of resistance to Rice yellow mottle virus (RYMV) in the African rice species Oryza glaberrima - (:unkn) unknown (My University, 2016)
The Rice yellow mottle virus (RYMV) is a major constraint for rice production in Africa. Two genes controlling recessive resistances have been previously described : RYMV1 coding for eIF(iso)4G1, a translation initiation factor, and RYMV2, coding for CPR5-1, a probable component of the nuclear pore complex involved in the regulation of defense mechanisms. However, the virus' ability to overcome these resistances highlight the need to characterize new sources of resistance in the African rice species O. glaberrima and O. barthii. Three complementary approaches were carried out in order to identify the genetic factors controlling these resistances.A genetic mapping strategy in bi-parental populations led to the identification of the RYMV3 gene, controlling resistance in the Tog5307 accession and probably also in the Tog5672 accession. It is the first dominant resistance identified in the rice/RYMV pathosystem. RYMV3 mapped in a 15 kb interval in which two genes annotated occur, including one NB-LRR gene.The two other strategies used were based on the utilization of Illumina sequencing data of 163 O. glaberrima accessions and 84 O. barthii accessions. O. glaberrima accessions were phenotyped for both high and partial resistance to RYMV, and the high resistance of a portion of the O. barthii accessions was assessed. Analysis of allelic variability at the previously identified genes led to the identification of a probable new resistance allele at RYMV1 and of six others at RYMV2. These alleles are currently undergoing validation. Furthermore, a genome wide association study was carried out on 125 O. glaberrima accessions, revealing two partial resistance QTLs on chromosomes 6 and 11, including one colocalized with RYMV3.This work has thus allowed the identification of one major resistance gene, of two QTLs and of new resistance alleles, contributing to a better understanding of rice/RYMV interactions and creating new prospects for the breeding for resistan
Keywords: African Research